Experiences of internationally educated nurses working with older adults: A scoping review protocol. - Kristina M Kokorelias; Marianne Saragosa; Reham Abdelhalim; Eleni Philippopoulos; Ann Vo (PLoS ONE)
Background Canada, like many other jurisdictions worldwide, is facing a nursing shortage. At the same time, high-income countries are facing a rapidly ageing and more complex older adult population. Demands for more responsive health care services are driving systems of care to meet the evolving needs of the ageing population. Internationally-educated nurses (IENs) can help fill gaps in the care of older adults, but may need considerable support to work in new social and health care environments. However, the experiences of IENs within the geriatric care literature have not been comprehensively reviewed. This protocol will outline a scoping review to determine: (1) what is known about the experiences and support needs of IENs in geriatric healthcare settings within high income countries? (2) what are current supportive-pathways for IENs in geriatric practice settings? And (3) what are the research gaps in the existing literature on the experiences and support needs of IENs within the context of geriatrics? Methods A scoping review will be conducted guided by the methodological framework set out by Arksey and O'Malley (2005) and later advanced by Levac, Colquhoun and O'Brien (2010). The search strategy will be applied to seven databases (MEDLINE, PubMed (non-MEDLINE records), PsycINFO, PsychArticles, CINAHL, Scopus, Web of Science). Grey literature will be searched using Google search engines, targeted websites and consultation with content experts. Articles of any publication date will be included. A two-stage screening process will be conducted in duplicate (i.e., two reviewers per stage) to determine eligible articles. Data from eligible articles will be extracted using a piloted charting form. Extracted data will be analyzed using thematic and descriptive analyses. Discussion The findings of the upcoming will highlight opportunities and recommendations to inform future research and support training to support IENs working with older adults within high income countries. Publication, presentations and stakeholder meetings will disseminate our findings.